Covariance of Phytoplankton, Bacteria, and Zooplankton Communities Within Microcystis Blooms in San Francisco Estuary - Lehman, Peggy W.; Kurobe, Tomofumi; Huynh, Khiet; Lesmeister, Sarah; Teh, Swee J. (Frontiers in Microbiology, 2021)
Microcystis blooms have occurred in upper San Francisco Estuary (USFE) since 1999, but their potential impacts on plankton communities have not been fully quantified. Five years of field data collected from stations across the freshwater reaches of the estuary were used to identify the plankton communities that covaried with Microcystis blooms including non-photosynthetic bacteria, cyanobacteria, phytoplankton, zooplankton and benthic genera using a suite of analyses including microscopy, qPCR and shotgun metagenomic analysis. Coherence between the abundance of Microcystis and members of the plankton community was determined by hierarchal cluster analysis (CLUSTER) and type 3 similarity profile analysis (SIMPROF), as well as correlation analysis. Microcystis abundance varied with many cyanobacteria and phytoplankton genera and was most closely correlated with the non-toxic cyanobacterium Merismopoedia, the green algae Monoraphidium and Chlamydomonas, and the potentially toxic cyanobacteria Pseudoanabaena, Dolichospermum, Planktothrix, Sphaerospermopsis and Aphanizomenon. Among non-photosynthetic bacteria, the xenobiotic bacterium Phenylobacterium was the most closely correlated with Microcystis abundance. The coherence of DNA sequences for phyla across trophic levels in the plankton community also demonstrated the decrease in large zooplankton and increase in small zooplankton during blooms. The breadth of correlations between Microcystis and plankton across trophic levels suggests Microcystis influences ecosystem production through bottom-up control during blooms. Importantly, the abundance of Microcystis and other members of the plankton community varied with wet and dry conditions, indicating climate was a significant driver of trophic structure during blooms.